Pengaruh Karakteristik Peternak Melalui Kompetensi Peternak terhadap Kinerja Usaha Ternak Sapi Potong di Kabupaten Bandung - Diyani Fauziyah; Rita Nurmalina; Burhanuddin Burhanuddin (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2015)
This research aims to: (1) identify characteristics and competencies of beef cattle farmer, and (2) analyze the influence of characteristics through competencies of farmer on business performance of beef cattle farm in Bandung Regency. In this research, the farmer characteristics consist of personal and psychological characteristic, whereas the competencies consist of technical and entrepreneurial competency. This research used 121 data of beef cattle farmers that collected by proportional cluster sampling according to the central areas of the farm, namely Cikancung, Cimenyan, and Cimaung Districts. The data were analyzed by SEM (Structural Equation Modeling) analysis. The results showed that both characteristics positively and significantly influence both competencies, and also have an indirect effect on business performance by technical competency. Psychological characteristic (need for achievement as a strong predictor) more influential on competencies than personal characteristic (informal education as a strong predictor). Technical competency (managing marketing and input as a strong predictor) positively (γ=0.81) and significantly influence the business performance (productivity as a strong predictor), while the influence of entrepreneurial competency is not significant. Indirectly, psychological characteristic (0.56) more influential on business performance than personal characteristic (0.29). The implication, beef cattle productivity can be increased by improving technical competency, especially for managing marketing and input. This competency can be improved by increasing need for achievement and active participation of farmers in attending the counseling/training by giving them rewards.